Endogenous Cardiotonics: Search and Problems - Kolpakov, Arkady R.; Knyazev, Roman A. (Cardiovascular & Haematological Disorders - Drug Targets, 2021)
Medicinal preparations currently used for the treatment of patients with chronic cardiac failure involve those that reduce the heart load (vasodilators, diuretics, beta-blockers, and angiotensin- converting enzyme (ACE) inhibitors). Cardiotonic drugs with the cAMP-dependent mechanism are unsuitable for long-term administration due to the intensification of metabolic processes and an increase in the oxygen demand of the myocardium and all tissues of the body. For many years, digoxin has remained the only preparation enhancing the efficiency of myocardial performance. The detection of digoxin and ouabain in intact animals has initiated a search for other compounds with cardiotonic activity. The review summarizes current data on the effect exerted on the heart performance by endogenous compounds, from simple, such as NO and CO, to steroids, fatty acids, polypeptides, and proteins. Controversial questions and problems with the introduction of scientific achievements into clinical practice are discussed. The results obtained by the authors and their colleagues after many years of studies on the cardiotropic properties of serum lipoproteins are also reported. The experimentally established cardiotonic activity of apoprotein A-1, which is accompanied by a decrease in the relative consumption of oxygen, maybe of great interest.
Keywords: apoprotein A-1